Metode Pembuatan Guludan Secara Mekanis denganTenaga Penggerak Traktor Dua Roda untuk Budidaya Tanaman Sayuran - Wawan Hermawan; Desrial .; Susanto Budi Sulistyo (PERTETA, 2009)
The objective of this study was to determine the best tillage method for making planting beds forvegetables cultivation using a two-wheel type tractor. Five tillage methods using a two-wheel type tractorwith its equipments were tested and evaluated in this study. The methods which were tested were: 1)plowing using a reversible type plow, followed by ridging using a ridger and finished by harrowing using arotary tiller (B-F-G 1 method) ; 2) plowing, followed by harrowing and finished by ridging (B-G-F method);3) plowing, followed by harrowing followed by ridging and finished by 2nd harrowing (B-G-F-G method); 4)plowing, followed by 40 cm width of harrowing and finished by ridging (B-G-F 2 method); and 5) plowing,followed by 40 cm width of harrowing and finished by ridging with 40 cm tractor wheel-base (B-G-F 3method). The experiments were conducted on several plots of dry land. The results of the experimentsshowed that the B-G-F 3 method produced the best planting bed form, an appropriate bed size and abetter soil condition for vegetables cultivation. The field capacity of this method was 74 m2/hour and wasthe highest capacity among the five methods.Keywords: planting bed, two wheel tractor, tillage, vegetable cultivationDiterima: 9 Desember 2008; Disetujui: 20 Maret 2009